Регулирование продовольственного рынка: рынок молока Украины - Кундеева, Галина Алексеевна (My University, 2012)
Проведены исследования экономической конъюнктуры рынка как формы проявления на рынке системных факторов, выражающейся в определенном соотношении спроса, предложения и динамике цен. Разработаны рекомендации по регулированию продовольственного рынка Theoretical researches of basic indexes of food safety, which the criteria of estimation of national food safety of country are offered on the basis of, are conducted, gradation of physical availability of food is considered. Basic factors which have influence on the state of the food providing and the row of measures is offered on their liquidation are certain
Keywords: коэффициент продовольственной зависимости; критерий энергетического удовлетворения; показатель физической доступности продовольствия; coefficient of food dependence; criterion of power satisfaction; to physical availability of food; кафедра економічної теорії